Efficient PML formulations for truncating nonlinear FDTD domains - Ramadan, O (IEEE, 2005)
In this paper, efficient formulations of the Perfectly Matched Layer (PML) are presented for truncating Nonlinear Finite Difference Time Domain (FDTD) grids. The proposed scheme is based on the Z-transform theory and the stretched coordinates PML formulations. The formulations are validated through numerical example carried out in one dimensional domain which includes Lorentz dispersion as well as Kerr and Raman nonlinearities.
Workshop on Computational Electromagnetics in Time-Domain -- SEP 12-14, 2005 -- Georgia Tech, Technol Square Res Bldg, Atlanta, GA
Keywords: finite difference time domain; perfectly matched layer; Lorentz; nonlinear; Kerr; Raman; soliton; Z-transform